Isokinetic performance, functionality, and pain level before and after lumbar and pelvic estabilization exercise in individuals with chronic low back pain - Jarbas Melo Filho; Fernanda Maria Cercal Eduardo; Auristela Duarte de Lima Moser (Fisioterapia em Movimento)
Introduction Chronic low back pain with a mechanical and degenerative origin is among the most common symptoms experienced by people all over the world. Objective To analyze the effects of a protocol for lumbar and pelvic segmental stabilization with regard to isokinetic variables, functionality, and pain in patients with low back pain. Materials and methods The sample consisted of 21 subjects, 8 female and 13 male, with a mean age of 42.6 ± 12.5 years. We used tests for mobility (modified Schober index), flexibility (finger-floor distance), functionality (Roland-Morris questionnaire), pain (Visual Analog Scale of Pain), and the isokinetic variables torque peak, work, flexors/extensors ratio before and after application of a protocol for segmental stabilization in subjects with chronic low back pain with a mechanical and degenerative origin. This protocol was used for two months, being applied twice a week. The data were statistically tested by means of the software Statistica, version 8.0. Results There were significant improvements for the variables flexibility (p = 0.014), functionality (p < 0.001), pain level (p < 0.001), torque peak flexion (p = 0.008), torque peak range (p < 0.001), torque flexion (p = 0.001), torque range (p < 0.001), and flexors/extensors ratio (p = 0.001). Conclusion Even with the improved levels of trunk muscles strength, both flexors and extensors, it was not possible to rebalance the segment according to data available in the literature. It is believed that there is a need for a protocol with a longer application period, maintaining the recruitment of extensor muscles. Regarding mobility of the lumbar segment, the protocol showed no significant differences in post-treatment (p = 0.520). This may be attributed to improved muscle control, providing the increased passive stiffness required to promote stability.